PENGARUH BELANJA MODAL TERHADAP PERTUMBUHAN KINERJA KEUANGAN DAERAH DENGAN PENDAPATAN ASLI DAERAH SEBAGAI VARIABEL INTERVENING (Studi Kasus di Propinsi Jawa Tengah) - Fajar Nugroho; Abdul Rohman (Diponegoro Journal of Accounting, 2012)
The research aims to analyze the influence of Capital Expenditure for finansial performance growth through revenue affluent as intervening variables. This research refers to a previous research’s conducted by Asha Florida (2007). Objects of this research is the entire district and city in Central Java province.The research was carried out by the method of documentation. The data used are secondary data, which comes from the realization of the Budget Report Revenue and Expenditure (Budget) of the city district in Central Java from 2008 until 2010.The results of this study indicate that the Capital Expenditures negatively affect the growth of the region's financial performance directly, whereas indirect positive effect on Capital Spending Growth through Revenue Financial Performance as an intervening variable region.